Assessment of Solar Orientation and Shading Devices in Reducing Cooling Loads in Educational Buildings - Binti, Sarina Julien; Wantouw, Sonny (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2025)
This study assesses the effectiveness of solar orientation and shading devices in reducing cooling loads in educational buildings through a qualitative literature review approach. As educational facilities are significant energy consumers, especially in hot climates, optimizing building orientation and integrating passive shading strategies are crucial for enhancing energy efficiency and thermal comfort. The literature indicates that building orientation significantly influences solar heat gain, with north-facing orientations generally resulting in lower internal temperatures and reduced cooling demands compared to east or west-facing layouts. Shading devices, including fixed external shades and optimized window-to-wall ratios, further mitigate direct solar radiation, contributing to notable reductions in annual energy consumption. Studies reviewed demonstrate that the combination of optimal orientation and well-designed shading can decrease cooling loads by 11% to 23%, and overall energy use by up to 44%. However, the effectiveness of shading devices depends on their design, placement, and integration with other passive strategies. While fixed shading reduces solar gains, occasional glare and insufficient daylight distribution may persist, indicating the need for a holistic design approach. The findings underscore the importance of integrating solar orientation and shading devices in the early design phase of educational buildings to achieve sustainable, energy-efficient, and comfortable learning environments. This research provides valuable insights for architects, planners, and policymakers seeking to implement best practices in sustainable school design, particularly in regions with high cooling demands.